Effect of fuel treatments and backfiring on the recovery of an obligate seeder-dominated heathland - Fernández Filgueira, Cristina; Vega Hidalgo, José A. (Forest Systems, 2016)
Aim of study: To evaluate how a plant community responded to a backfire that occurred four years after application of different types of fuel-reduction treatments.Area of study: Erica umbellata Loefl. (L.)-dominated heathland in Galicia (NW Spain).Materials and Methods: Shrub cover surveys in 16 experimental plots from 2006 to 2014. Fuel reduction treatments (prescribed burning, clearing and mastication) were applied in the spring of 2006 and the area was burned by a wildfire in the summer of 2010.Main results: Shrub total cover recovered quickly after the backfire in both the treated and untreated areas, and the pre-treatment values were reached four years after the fire. Post-wildfire resprouting species cover recovery was not affected by fuel treatments. As a contrast,  Erica umbellata cover reached levels similar to those in the untreated plots only in the areas treated by prescribed burning. After the wildfire, grasses cover recovery was greater in the treated than in the untreated areas and the effect lasted until the end of the study.Research highlights: Prescribed fire and backfire was favourable for Erica umbellata regeneration compared to clearing and mastication.Keywords: prescribed burning; clearing; mechanical shredding; Erica; wildfire.